Exposure to sexism can decrease implicit stereotype bias - Ramos, M. R. (2016)
Two studies examined the effect of exposure to sexism on implicit gender bias, focusing specifically on stereotypes of men as competent and women as warm. Male and female participants were exposed to sexism or no sexism. In both Experiment 1 ( Implicit Association Task; N=115) and Experiment 2 ( Go/No-go Association Task; N=167), women who had been exposed to sexist beliefs demonstrated less implicit gender stereotype bias relative to women who were not exposed to sexism. In contrast, exposure to sexism did not influence men's implicit gender stereotype bias. In Experiment 2, process modelling revealed that women's reduction in bias in response to sexism was related to increased accuracy orientation and a tendency to make warmth versus competence judgments. The implications of these findings for current understandings of sexism and its effects on gender stereotypes are discussed.